Estimating Junior School-Age Children’s Mastery of Complex Movements Applying Parametric Teaching (Baltic Journal of Sport and Health Sciences, 2018)
After realizing the fact that learning new movements and actions is efficient only in the case when the child is capable of applying the movement or action learnt under new conditions, when the skill acquired is remembered and retained for long the authors (Schmidt, 1988, 1991; Schmidt, Lee, 1999; Skurvydas, 1998; Skurvydas, Gedvilas, 2000) have singled out and defined the parametric teaching of movements. Therefore the following research problem arises: is the parametric method of teaching effective in teaching children of junior school-age to perform complex movements and actions, as well as to retain them for long and apply them under new conditions. The aim of the research was to establish and estimate the efficiency of the parametric method and mastery in teaching children of the junior school age the accuracy of movements, retaining power and creativity of the complex movements learnt. With a view to find out the efficiency of parametric teaching a pedagogical experiment with junior schoolchildren (n = 67) aged 8—10 years was carried out. During all teaching stages the program of the movements taught was applied in the period of 7—8 weeks. In this period the observation of the development of mastering new movements in the standard teaching group and in that of parametric teaching took place. During the following 2 months the efficiency of standard and parametric teaching applied was observed, i. e. the ability to retain the movements learnt for as long as possible. We can conclude that the more relatively complicated movements and actions are taught the less difference between efficiency of standard teaching and parametric teaching is found: when teaching complicated accuracy requiring movements using both standard and parametric methods, development and level of mastering are adequate; when teaching complicated locomotive movements, the children of standard teaching group master the movements more rapidly; when teaching complicated high accuracy requiring combinations of locomotive movements under standard and variable conditions, the indices of development of mastering did not differ essentially. The children of standard and parametric teaching groups retained and reproduced (after 1 and 2 months) complicated movements of different degree of complexity in a different way: the children who had been taught under variable conditions markedly better retained and reproduced both complicated locomotive and complicated locomotive movements requiring accuracy; the children of parametric teaching groups who had been taught the same movements and their combinations under conditions of change in parameters of high degree, better retained and reproduced the movements than the children of other parametric teaching groups. The efficiency of standard and parametric teaching of complicated movements for children’s abilities to retain them for a longer period of time, reproduce and apply them in new circumstances — creativity of movements — depends on the character of the circumstances changed: the children of parametric teaching groups in new circumstances by a long way better retained and reproduced movements previously learnt which were complicated locomotive ones when structure of a movement was altering and necessity to make a choice existed.Keywords: parametric teaching, teaching children under standard and variable conditions, junior school-age (8—10 years).